Patterns of intimate partner violence among black women in community supervision programs who use drugs: a latent class analysis - Ariel Richer; Dawn Goddard-Eckrich; Mingway Chang; Elwin Wu; Brooke West; Nabila El-Bassel; Louisa Gilbert (Health & Justice)
Abstract Background Intimate partner violence (IPV) disproportionately affects Black women who use drugs and those mandated to community supervision programs (CSPs). Societal responses to minoritized identities such as being a woman who has sex with women and men (WSWM) and using substances further increases the risk. This study sought to 1) identify patterns of IPV perpetrated by male partners and 2) examine membership to latent classes and associations to WSWM and other sociodemographic and psychosocial factors. This is a secondary data analysis using baseline survey data from the E-WORTH randomized control trial (2015 – 2019) that evaluated the effectiveness of an HIV/STI intervention for Black women who use drugs mandated to CSPs (n = 272). Descriptive and bivariate analysis were used to describe psychosocial and sociodemographic factors. Latent class analysis was conducted on responses to the Revised Conflict Tactics Scale lifetime psychological, physical, injurious, and sexual items, to identify latent classes of women who experienced IPV. Results Forty-one percent (n = 144) of the sample were WSWM, 89% of whom experienced lifetime IPV. WSWM experienced significantly higher rates of all types of IPV. LCA revealed a two-class solution was the best fit: Class 1 (High Psychological/Low-Moderate Other IPV) and Class 2 (High Psychological & Physical IPV/Moderate Injurious & Sexual IPV). Two thirds of the sample were members of Class 2 and had an overall moderate to high probability of experiencing each type of IPV. WSWM, any lifetime illicit drug use, childhood physical or sexual abuse, and lifetime experience of police sexual misconduct were associated with higher odds of membership to Class 2, compared to membership to Class 1. Conclusion Experiencing minoritized identities and related psychosocial factors is associated with higher rates of all types of IPV. Inclusive IPV services are needed to engage Black WSWM who use drugs within the criminal-legal system.